1979
DOI: 10.1007/bf00586943
|View full text |Cite
|
Sign up to set email alerts
|

The cholinergic pathway to cerebral blood vessels

Abstract: The effect of stimulating the greater superficial petrosal nerve (g.s.p.n.) upon retroglenoid venous blood flow has been tested in anaesthetized, paralysed and artificially ventilated rats. In 11 out of 15 tests, blood flow increased by an average of 25% with a time to peak response of 28 s. This response was abolished with the injection of atropine 0.1 mg kg-1 injected intra-arterially. With both petrosal nerves intact, the administration of 6-7% CO2 in air or 15% O2 in N2 caused average increases in blood fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1982
1982
1995
1995

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…Results of the present study are in conflict with some in vivo findings that atropine blocks both pial vessel dilation and increased cerebral blood flow following electrical stimulation of the superficial petrosal nerve (Cobb and Finesinger, 1932;Vasquez and Purves, 1977;D'Alecy, 1977;Pinard et al, 1979). As we have suggested (Lee, 1980), one possible explanation for the discrepancy between in vitro and in vivo findings is that ACh may be involved in the dilator pathway at sites other than the terminal synapse.…”
Section: Figure 7 Effect Of Cold Storage On Transmural Nerve Stimulacontrasting
confidence: 80%
“…Results of the present study are in conflict with some in vivo findings that atropine blocks both pial vessel dilation and increased cerebral blood flow following electrical stimulation of the superficial petrosal nerve (Cobb and Finesinger, 1932;Vasquez and Purves, 1977;D'Alecy, 1977;Pinard et al, 1979). As we have suggested (Lee, 1980), one possible explanation for the discrepancy between in vitro and in vivo findings is that ACh may be involved in the dilator pathway at sites other than the terminal synapse.…”
Section: Figure 7 Effect Of Cold Storage On Transmural Nerve Stimulacontrasting
confidence: 80%
“…The cerebral vessels are richly supplied by cholinergic as well as sympathetic and peptidergic nerves and express much greater ACh contents than most extracranial vessels (Bevan et al, 1982;Duckles, 1981;Suzuki and Hardebo, 1993), al though the role of innervation in the regulation of CBF is still controversial. In the resting condition, even an electric stimulation of the Vth or VIIth cra nial nerves had a small or minimal effect on regional CBF (Busija and Heistad, 1981;Pinard et al, 1979). We recently reported that the intravenous ad ministration of phenoxybenzamine, an a-blocker (Shiokawa et al, 1989), or captopril, an angioten sin-converting enzyme inhibitor (Sadoshima et al, 1994) that decreases cerebrovascular sympathetic tone, shifts the lower limits of autoregulation to the lower levels of blood pressure with the reduction of vascular resistance in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…Chorobski and Penfield (1932) in monkey and Za charias (1945) in rat. The projections of this gan glion have not been fully elucidated, but the gan glion cells display AChE reactivity (Vasquez and Purves, 1979), some cells are VIP positive (Suzuki et aI. , 1988), and in the caudal part of the ganglion substance P-and calcitonin gene-related peptide positive cells are found (Hardebo et aI., 1989;Su zuki et aI., 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Key Words: Cerebral blood vessels-Choline acetyltransferase-Cerebro vascular innervation-Parasympathetic nerves Retrograde axonal tracing-Vasoactive intestinal poly peptide 1982), rat (Edvinsson et al, 1972;Licata et aI. , 1975;Vasquez and Purves, 1979;Kobayashi et aI., 1983;Hara et al, 1985;Hara and Weir, 1986), mouse, hamster, guinea pig, and cat (Edvinsson et al , 1972). All these histochemical studies were ex clusively based on nerve staining for AChE, origi nally developed by Koelle and Friedenwald (1949).…”
mentioning
confidence: 99%